A randomized controlled efficacy trial of an mHealth HIV prevention intervention for sexual minority young men: MyPEEPS mobile study protocol - Kuhns, Lisa M. (BMC Public Health, 2020)
BACKGROUND: Young sexual minority men in the United States have a high incidence rate of HIV infection. Early intervention among this group, that is timed to precede or coincide with sexual initiation, is of critical importance to prevent HIV infection. Despite this, there are very few published randomized controlled efficacy trials testing interventions to reduce sexual vulnerability for HIV acquisition among racially/ethnically diverse, very young, sexual minority men (aged ≤18 years). This paper describes the design of a mobile app-based intervention trial to reduce sexual risk for HIV acquisition and promote health protection in this group. METHODS: This study is a randomized controlled trial of an mHealth-based HIV prevention intervention, MyPEEPS Mobile, among diverse sexual minority cisgender young men, aged 13–18 years. The mobile intervention was adapted from a prior group-based intervention curriculum with evidence of efficacy, designed to be specific to the risk contexts and realities of young sexual minority men, and to include psychoeducational and skill-building components with interactive games and activities. Participants are recruited locally within four regional hubs (Birmingham, AL, Chicago, IL, New York City, NY, Seattle, WA) and nationwide via the Internet, enrolled in-person or remotely (via videoconference), and randomized (1:1) to either the MyPEEPS Mobile intervention or delayed intervention condition. Post-hoc stratification by age, race/ethnicity, and urban/suburban vs. rural statuses is used to ensure diversity in the sample. The primary outcomes are number of male anal sex partners and frequency of sexual acts with male partners (with and without condoms), sex under the influence of substances, and uptake of pre-and post-exposure prophylaxis, as well as testing for HIV and other sexually transmitted infections at 3-, 6- and 9-month follow-up. DISCUSSION: Behavioral interventions for very young sexual minority men are needed to prevent sexual risk early in their sexual development and maturation. This study will provide evidence to determine feasibility and efficacy of a mobile app-based HIV prevention intervention to reduce sexual risk among this very young group. TRIAL REGISTRATION: ClinicalTrials.gov number, NCT03167606, registered May 30, 2017.